An Expert System Shell for Lexicographic Research - Choul, Jean-Claude (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1989)
This paper is an informal présentation of LEXIC, a dictionary editing shell combining a relational database and an expert system using both forward and backward chaining for consultation, which will be contrasted with LEXPERT, a dictionary prototype in the form of a diagnostic expert system. This is not an in-depth introduction to shells in general nor to databases or expert systems. I will assume from my audience little or no knowledge of these and supply concise working definitions. I apologize to those who already have practical or theoretical training or information on the various topics. Personally, I started working with expert systems and relational databases this year, in January, while looking for a computerized application of my work in semantics presented as a doctoral dissertation (Doctorat d’État) at the Sorbonne in 1987. This should eventually result in a computerized prototype of sense assignment using production rules.